Examining the Associations of and Interactions Between Intrapersonal and Perceived Environmental Factors With Objectively Assessed Physical Activity Among Rural Midwestern Adults, USA. Issue 4 (May 2023) - Serrano, Natalicio; Beck, Alan; Salvo, Deborah; Eyler, Amy; Reis, Rodrigo; Steensma, Joseph T.; Gilbert, Amanda; Brownson, Ross C.
Purpose: We investigated associations of intrapersonal and environmental factors with objectively assessed weekly moderate to vigorous physical activity (MVPA) minutes, and their interactions in rural adults. Design: Cross-sectional. Setting: 14 rural towns participating in a multilevel intervention to promote physical activity. Sample: Baseline data from 241 rural community members (19% losses due to missing data). Measures: Self-reported demographics, behavioral factors, and neighborhood environment perceptions. Weekly MVPA minutes were assessed using accelerometry data. Analysis: Generalized linear models using a negative binomial distribution examined associations of and interactions between intrapersonal and environmental correlates with weekly MVPA. Results: Older age (β = −1.37; P = .025) and identifying as a woman (β = −.71; p= <.001) were inversely associated with MVPA. Self-efficacy (β = .34; p = <.001) and trail use (β = .44; P -value = .003) were directly associated with MVPA. Further, among women, perceived safety from traffic was inversely associated with MVPA (β = −.37; P = .003), while indoor recreational facility access was directly associated with MVPA (β = .24; P = .045). Conclusions: Rural residents, especially women, face disproportionately lower MVPA levels. Improving recreational access and self-efficacy may be effective strategies for increasing MVPA.